Inventarisasi Spesies Hama pada Tanaman Ubi Kayu (Manihot esculante Crantz) di Desa Tanjung Pering, Kabupaten Ogan Ilir, Sumatera Selatan - Gilang Putra Bintang; Dona Andreana; Juni Yanto; Alindia Marisa; Dian Putri Ayu; Shinta Kumala Dewi (xxxx-xxxx, 2023)
Bintang GP, Andreana D, Yanto J, Marisa A, Ayu DP, Dewi SK. 2022. Efficiency of rangrang ant (Oecophylla Smaragdina Fabrius) as predator of whitefly on chili plants (Capsicum annum L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Agustus 2022. pp. 1041-1048. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the main obstacles to cassava cultivation is pest attacks which can reduce production and are very detrimental to farmers. Species of pests on cassava plants include mealybugs, red mites and so on. These pests can cause direct damage to plants. This survey aimed to find out several species of pests found in cassava plants and to see firsthand the damage caused by these pests. The method used in this study is a survey method, namely observation (direct observation) on cassava plantations in Tanjung Pering Village, Ogan Ilir Regency, South Sumatra. Based on the results of this survey, the types of pests that attack the cassava plant (Manihot esculante Crantz) are the mealybug species (Phenacoccus manihoti Matile-Ferrero), the urethral pest species (Xylenthropus) and the red mite pest species (Tetranychus Urticae Koch). The mealybugs and red mites attack the leaves, precisely on the back of the leaf bones and for the urethic pests attack the underground roots. So, it can be concluded that there are three pests that attack cassava plants, namely red mites, mealybugs and uret which cause some damage to cassava plants. Preferably, in field surveys it would be better if you document using a macro lens to make it look clearer.